Reactions to cadmium stress in a cadmium-tolerant variety of cabbage (Brassica oleracea L.): is cadmium tolerance necessarily desirable in food crops? - Neel Jinadasa; Damian Collins; Paul Holford; Paul J. Milham; Jann P. Conroy (Environmental Science and Pollution Research, 2016)

Exposure to preindustrial, current and future atmospheric CO 2 and temperature differentially affects growth and photosynthesis in Eucalyptus - OULA GHANNOUM; NATHAN G. PHILLIPS; JANN P. CONROY; RENEE A. SMITH; RENEE D. ATTARD; ROSLYN WOODFIELD; BARRY A. LOGAN; JAMES D. LEWIS; DAVID T. TISSUE (Global Change Biology, 2010)
To investigate if Eucalyptus species have responded to industrial‐age climate change, and how they may respond to a future climate, we measured growth and physiology of fast‐ ( E. saligna ) and slow‐growing ( E. sideroxylon ) seedlings exposed to preindustrial (290), current (400) or projected (650 μL L −1 ) CO 2 concentration ([CO 2 ]) and to current or projected (current +4 °C) temperature. To evaluate maximum potential treatment responses, plants were grown with nonlimiting soil moisture. We found that: (1) E. sideroxylon responded more strongly to elevated [CO 2 ] than to elevated temperature, while E. saligna responded similarly to elevated [CO 2 ] and elevated temperature; (2) the transition from preindustrial to current [CO 2 ] did not enhance eucalypt plant growth under ambient temperature, despite enhancing photosynthesis; (3) the transition from current to future [CO 2 ] stimulated both photosynthesis and growth of eucalypts, independent of temperature; and (4) warming enhanced eucalypt growth, independent of future [CO 2 ], despite not affecting photosynthesis. These results suggest large potential carbon sequestration by eucalypts in a future world, and highlight the need to evaluate how future water availability may affect such responses.